Alpha-gal syndrome: public awareness, lived experiences, and health provider perspectives on plant-based nutrition - Sempa, Judith (My University, 2025)
There is a global rise in allergic conditions and multimorbidity. Historically, these have been treated as separate clinical entities however, emerging research indicates they share similar immunological roots primarily immune dysregulation. Alpha-gal syndrome (AGS), a tick-borne allergy triggered by lone star tick bites, is increasingly prevalent in the Southern, Eastern and mid-western regions of the United States including Kansas. Simultaneously, 10.2% of adults in Kansas experience multimorbidity (defined as having two or more chronic conditions such as obesity, chronic kidney disease, cardiovascular disease, cancer etc.). This study explored AGS awareness, distribution, lived experiences and systemic challenges faced by Kansans living with AGS. Using a mixed methods approach, the study included two anonymous surveys targeting Kansas community residents and Extension professionals, as well as in-depth interviews with thirty AGS-affected individuals. Findings revealed that while general awareness of AGS is growing, significant challenges remain related to dietary restrictions and adaptations, psychosocial challenges, financial burdens and gaps in healthcare support. Participants frequently relied on self-management and self-advocacy due to limited health professional knowledge and support, underscoring the need for improved medical education, clearer food labeling, and access to more support and resources. Our study found that many individuals with AGS adopted plant-based diets (PBDs) as a practical strategy for managing their condition. Emerging evidence indicates that PBDs, rich in antioxidant and anti-inflammatory compounds, can enhance gut health, support immune function, and reduce risk of chronic diseases by mitigating chronic systemic inflammation. Building on this insight, the third phase of the study examined health professionals’ readiness to support individuals following PBDs. A narrative review of 27 studies identified key barriers and enablers related to integration of PBDs in routine patient care which included: time constraints, limited educational resources, insufficient skills, limited interdisciplinary collaboration, and inadequate professional training. The study findings suggest that access to evidence-based research summaries, clear guidelines, ongoing professional development, and other relevant educational resources were crucial for equipping healthcare professionals to support individuals adopting PBDs which would benefit individuals managing AGS as well as those dealing with chronic diseases such as obesity, diabetes and cardiovascular disease. Overall, this study highlights two seemingly distinct yet interconnected public health challenges: (1) AGS, an emerging allergic condition that has become a leading cause of adult-onset allergies and anaphylaxis in high-prevalence areas; and (2) the critical need to equip healthcare professionals to effectively support individuals adopting a plant-based lifestyle. Given the growing body of evidence linking immune dysregulation to both allergic conditions and chronic disease pathogenesis, better understanding and integration of plant-based nutrition may offer dual benefits in the prevention and management of both.
Keywords: Alpha gal syndrome